PENGARUH KOMUNIKASI KERJA DAN PROFESIONALISME KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KEHUTANAN DAN LINGKUNGAN HIDUP PROVINSI BALI - Anggada Hardoyogi Tampubolon; Ni Putu Nina Eka Lestari (Universitas Triatma Mulya, 2023)
This research aims to determine the influence of work communication and work professionalism on the performance of Bali Province Forestry and Environment Service employees. The type of research used in this research is quantitative with a sample size of 76 respondents. The sampling technique in this research used random sampling technique. The data analysis technique used in this research is simple linear regression using the SPSS program. The results of this research show that first, work communication has a positive and significant effect on the performance of Bali Province Forestry and Environment Service employees. Second, work professionalism has a positive and significant effect on the performance of Bali Province Forestry and Environment Service employees. Third, work communication and work professionalism simultaneously influence the performance of Bali Province Forestry and Environment Service employees.